2020
DOI: 10.1007/s00406-020-01145-8
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity and connectivity differences in reward value discrimination during effort computation in schizophrenia

Abstract: Brain activity and connectivity differences in reward value discrimination during effort computation in schizophrenia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 54 publications
1
8
1
Order By: Relevance
“…In our task this reward maximization strategy may be successful even when effort cannot consistently be maintained, because participants received the default reward of 1 CHF in failed trials. However, in both our task, and that of Pretus et al, 44 reward maximization in patients was not observed: in the former we find no difference between patients and controls in the amount won, and in the latter patients ended up with lesser total gains than controls.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In our task this reward maximization strategy may be successful even when effort cannot consistently be maintained, because participants received the default reward of 1 CHF in failed trials. However, in both our task, and that of Pretus et al, 44 reward maximization in patients was not observed: in the former we find no difference between patients and controls in the amount won, and in the latter patients ended up with lesser total gains than controls.…”
Section: Discussioncontrasting
confidence: 65%
“…A recent study using an effort-based task (in the form of button presses) in patients with SZ and HC participants has also reported that patients made high-effort choices irrespective of the reward amount they could win (1 euro vs 1 cent). 44 It thus appears that in certain circumstances patients with SZ tend to disregard effort to maximize reward. This strategy may appear rational, as indeed, if the high effort can be maintained throughout the task, this should result in maximizing reward.…”
Section: Discussionmentioning
confidence: 99%
“…For example, those with early psychosis were less likely to select the high-effort, high-reward options than healthy control subjects ( 94 ). Furthermore, in a task in which increasing the effort improved the chance of receiving a high or low reward, people with schizophrenia were willing to expend the same effort regardless of reward size, whereas healthy individuals heavily biased their effort to increase the chance of higher rewards ( 95 ). This was associated with reduced functional changes in the caudate and anterior cingulate cortex during reward presentation and in the caudate during effort selection.…”
Section: Reward Processing In Psychosismentioning
confidence: 99%
“…The primary search yielded 1592 studies published between 1971 and 2021 (Figure 1). Overall, 20 references had usable data and were included in the meta-analysis . Studies represented a total of 1503 participants, of whom 666 were controls (306 [45.9%] female; 360 [54.1%] male; mean [SD] age, 34.16 [5.92] years) and 837 had schizophrenia (296 [35.4%] female; 541 [64.6%] male; mean [SD] age, 35.89 [6.70] years).…”
Section: Resultsmentioning
confidence: 99%
“…Another controversial issue is the confounding effect of antipsychotic medications on effort-cost computation. Multiple studies found no correlation between antipsychotic dose and willingness to exert effort, while one study found a positive association; this is surprising given the implication of acute striatal dopamine D 2 blockade in reducing goal-directed behavior …”
Section: Introductionmentioning
confidence: 95%